Analisis Economic Value Added (EVA) dan Return on Asset (ROA) untuk menilai kinerja keuangan pada BPJS Ketenagakerjaan - Salsabilla Azzahra; Ruzikna Ruzikna (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to assess the financial performance of BPJS Employment for the period 2017 to 2021 based on the EVA and ROA methods. The data used in this study is in the form of financial report data for the years 20172021. The analytical method used is descriptive analysis method. From the analysis of data based on EVA and ROA methods, it shows good performance even though during the last five years it has fluctuated every year, BPJS Ketenagakerjaan is able to manage the problem optimally. The results of the analysis of the EVA method show a positive value (EVA > 0), meaning that the company is able to create added value for its shareholders, while the results of the ROA analysis have an average value of 3% which is in the healthy category, This means that the company is able to manage its assets properly so as to obtain optimal profit.